Conversations Across Continents: Teaching Business Ethics Online - Painter-Morland, Mollie (Journal of business ethics, 2003)
The paper focuses on an online business ethics course that three professors (Painter-Morland, Fontrodona and Hoffman) taught together, and in which the fourth author (Rowe) participated as a student, from their respective locations on three continents. The course was conducted using Centra software, which allowed for synchronous online interaction. The class included students from Europe, South Africa and the United States. In order to assess the value of synchronous online teaching for ethics training, the paper identifies certain knowledge, skills and capacities that are crucial to the moral development process within individuals. The paper argues that the online teaching method succeeds in creating an environment within which important ethical knowledge and skills might be developed. It provides an in-depth reflection on the advantages and dis-advantages of online teaching and proposes improvements on the way forward. One of the major advantages relates to its ability to facilitate cross-cultural discussion and debate on ethical issues and foster insight into contextual influences on ethics management within an international arena.